CHES robotic observation software kit - Zhang, Chen; Zhu, Can (Frontiers in Astronomy and Space Sciences, 2022)
CHES (CHanging Event Survey) is an optical survey program that aims at searching fast-moving RSOs in the sky for Space Domain Awareness, but also takes other scientific goals into account, such as NEO and transient events. After the success of the first array located at the Yaoan site in China, it evolved into a wider network consisting of various types of devices. This paper presents a full-function framework for coordinating observation across such a network. The robotic observation system takes both extension flexibility and operation simplicity into account to meet special requirements such as timing, complex tracking, dynamic scheduling, unique device configuration and distributed collaborative observation. Currently, this Python-based system has been deployed to several sites, supporting observation systems from single, entry-level telescopes to multiple medium-sized professional telescopes, performing predefined routing surveys and user-defined observation for different scientific goals. Some of them run unattended for a regular survey to maintain the base catalog and produce survey images for different purposes.